Experimental investigation on the mechanical behaviour of AAC blocks for sustainable concrete masonry - Elena Michelini; Daniele Ferretti; Alice Sirico; Roberto Cerioni (Acta Polytechnica CTU Proceedings)
To satisfy the increasing demand of energy efficient buildings, AAC manufacturers are nowadays encouraged to produce blocks with ever lower densities. However, a compromise between energy-saving requirements and mechanical performances is needed to ensure structural safety, as well as an adequate structural durability. This paper reports a comprehensive experimental study on AAC mechanical properties (compressive and tensile strengths, as well as fracture energy), and on their dependency from material density and moisture content. The collected data are compared with some well-known analytical relations taken from the literature, which are often used for the calibration of mechanical parameters required for mathematical and/or finite element modelling of AAC load-bearing masonry, as well as of AAC masonry-infilled framed structures. These comparisons highlight some critical issues in the formulation of analytical relations having a general applicability; however, it was found that RILEM suggestions are appropriate for the considered AAC productions, at least for densities greater than 400 kg/m3.